Telesimulation for the Training of Medical Students in Neonatal Resuscitation - Lukas P. Mileder; Michael Bereiter; Bernhard Schwaberger; Thomas Wegscheider (MDPI AG, 2023)
Background: Telesimulation may be an alternative to face-to-face simulation-based training. Therefore, we investigated the effect of a single telesimulation training in inexperienced providers. Methods: First-year medical students were recruited for this prospective observational study. Participants received a low-fidelity mannequin and medical equipment for training purposes. The one-hour telesimulation session was delivered by an experienced trainer and broadcast via a video conference tool, covering all elements of the neonatal resuscitation algorithm. After the telesimulation training, each student underwent a standardized simulated scenario at our Clinical Skills Center. Performance was video-recorded and evaluated by a single neonatologist, using a composite score (maximum: 10 points). Pre- and post-training knowledge was assessed using a 20-question questionnaire. Results: Seven telesimulation sessions were held, with a total of 25 students participating. The median performance score was 6 (5-8). The median time until the first effective ventilation breath was 30.0 s (24.5-41.0) and the median number of effective ventilation breaths out of the first five ventilation attempts was 5 (4-5). Neonatal resuscitation knowledge scores increased significantly. Conclusions: Following a one-hour telesimulation session, students were able to perform most of the initial steps of the neonatal resuscitation algorithm effectively while demonstrating notable mask ventilation skills.